LUMBAR syndrome: A case manifesting as cutaneous infantile hemangiomas of the lower extremity, perineum and gluteal region, and a review of published work. Issue 7 (13th February 2017) - Yu, Xia; Zhang, Jia; Wu, Zhouwei; Liu, Ming; Chen, Ruhong; Gu, Yan; Li, Ming; Yao, Zhirong
Abstract: We herein report a rare case of LUMBAR syndrome. A 1‐month‐old female infant presented with extensive segmental hemangiomas on the left lower extremity, left perineum and gluteal region with ulceration. Bilateral labia minoras were asymmetrical. Both legs were asymmetrical with left leg atrophy, and the intergluteal cleft was deviated. A dark red pustule and a sacrococcygeal dimple could be seen in the lumbosacral region. Lipomyelomeningocele, tethered cord and sacrum dysplasia were noted by magnetic resonance imaging. The patient was found to have an absent left kidney at 32 weeks of pregnancy. Eventually, we draw the diagnosis of LUMBAR syndrome. In addition, we discuss the clinical manifestation, diagnosis, treatment and pathogenesis by a review of published work.